“Seeking Help is Difficult:” Considerations for Providing Mental Health Services to Muslim Women Clients - Saleem, Fatima; Martin, Stephanie L. (Canadian Journal of Counselling and Psychotherapy, 2018)
Mental health professionals who counsel Muslim women are well positioned to offer guidance on working with this underserved population. A basic interpretive qualitative research design was utilized to explore mental health professionals’ (N = 5) experience of providing counselling services to Muslim women. Analysis yielded four areas of consideration in the provision of counselling services to Muslim women: (a) difficulty of seeking help; (b) lack of awareness as a barrier; (c) need for community outreach, psychoeducation, and cross-cultural training; and (d) centrality of trust and careful application of modalities and orientations. Findings are described alongside implications for counselling practice, and directions for future research are identified.